Suprachoroidal Injection: A Novel Approach for Targeted Drug Delivery - Kevin Y. Wu; Jamie K. Fujioka; Tara Gholamian; Marian Zaharia; Simon D. Tran (MDPI AG, 2023)
Treating posterior segment and retinal diseases poses challenges due to the complex structures in the eye that act as robust barriers, limiting medication delivery and bioavailability. This necessitates frequent dosing, typically via eye drops or intravitreal injections, to manage diseases, often leading to side effects with long-term use. Suprachoroidal injection is a novel approach for targeted drug delivery to the posterior segment. The suprachoroidal space is the region between the sclera and the choroid and provides a potential route for minimally invasive medication delivery. Through a more targeted delivery to the posterior segment, this method offers advantages over other routes of administration, such as higher drug concentrations, increased bioavailability, and prolonged duration of action. Additionally, this approach minimizes the risk of corticosteroid-related adverse events such as cataracts and intraocular pressure elevation via compartmentalization. This review focuses on preclinical and clinical studies published between 2019 and 2023, highlighting the potential of suprachoroidal injection in treating a variety of posterior segment diseases. However, to fully harness its potential, more research is needed to address current challenges and limitations, such as the need for technological advancements, refinement of injection techniques, and consideration of cost and accessibility factors. Future studies exploring its use in conjunction with biotech products, gene therapies, and cell-based therapies can lead to personalized treatments that can revolutionize the field of ophthalmology.